Relational encoding promotes creative insight for problem-solving. - Kurtz, Kenneth J.; Haley, Leif; Longo, Alexus; Astra, Shanti; Meltzer, Hannah; Suwara, Gavin; Patterson, John D. (Memory & Cognition, 2025)
The nature and basis of creative thought has been the subject of wide-ranging inquiry. It is well established that people tend to struggle to solve problems that require an insight—and that this limitation is not readily alleviated. What can help produce more successful creative cognition? We propose a benefit from increased focus on the relations that hold between the elements of a problem situation. The present research addresses a novel technique to promote relational encoding by guiding participants to generate relational content connecting problem elements. In two experiments, we find that participants who engage in relational encoding are more likely to solve insight problems than controls. Theoretical and applied implications of the findings are addressed.